Composition Dependent Magnetic and Photocatalytic h2 Evolution Properties of Cds:Sm Nanoparticles - Radhalayam, D (Elsevier Ltd, 2024)
The fabrication of diluted magnetic semiconductors (DMSs) for spintronic devices has garnered significant recognition due to their diverse and impressive applications. Additionally, addressing global warming, replacing fossil fuels, and providing green energy are critical challenges of our time. In this context, we synthesized and characterized Sm-doped CdS nanoparticles, examining their magnetic, optical, structural, and photocatalytic hydrogen evolution properties for both spintronic and hydrogen fuel production applications. Structural analysis revealed that Sm ions successfully substituted Cd sites without altering the original structure. Optical studies demonstrated a reduction in the band gap with the incorporation of Sm ions into the CdS lattice, thereby enhancing the visible light absorption capabilities of the samples. Room temperature magnetic measurements indicated that while pristine CdS is paramagnetic, Sm-doped CdS nanoparticles exhibit strong ferromagnetic properties due to double exchange interactions among available spins, making them ideal for spintronic applications. Photocatalytic water splitting tests demonstrated that the CdS(4 at%) system achieved the highest hydrogen evolution rate among the samples, reaching 1629 μmol/g. We believe the CdS(4 at%) system is a promising candidate for efficient hydrogen fuel production under simulated sunlight irradiation, contributing to clean, renewable energy production. © 2024 Elsevier Ltd and Techna Group S.r.l.